Nomophobia and Self-Esteem: A Study of Migrant Students' Psychological Well-Being - Putri, Cantika Berlian Kusuma; Wibowo, Doddy Hendro (Guidance and Counseling Study Program, Pattimura University, 2024)
The transition from high school to higher education represents a significant milestone for adolescents, often accompanied by migration to access better educational opportunities, known as